The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1097/01.blo.0000148783.20469.4c
|View full text |Cite
|
Sign up to set email alerts
|

Wear, Debris, and Biologic Activity of Cross-linked Polyethylene in the Knee

Abstract: Cross-linked polyethylene currently is being introduced in knee prostheses. The wear rates, wear debris, and biologic reactivity of non cross-linked, moderately cross-linked, and highly cross-linked polyethylene have been compared in multidirectional wear tests and knee simulators. Multidirectional pin-on-plate wear studies of noncross-linked, moderately cross-linked (5 Mrad), and highly cross-linked (10 Mrad) polyethylene showed a 75% reduction in wear with the highly cross-linked material under kinematics fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
107
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(114 citation statements)
references
References 14 publications
3
107
2
2
Order By: Relevance
“…The improvement in wear performance in XLPE tibial inserts is supported by wear simulator experiments [12,22,33,34], but evidence of in vivo success is required for a comprehensive assessment. In our study, retrieval analysis was used to compare the accumulation of damage in vivo of conventional and highly crosslinked PE tibial plateaus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improvement in wear performance in XLPE tibial inserts is supported by wear simulator experiments [12,22,33,34], but evidence of in vivo success is required for a comprehensive assessment. In our study, retrieval analysis was used to compare the accumulation of damage in vivo of conventional and highly crosslinked PE tibial plateaus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, knee simulator studies use gravimetric methods to measure the amount of PE worn from the articulating surfaces [12,22,33,34]. Of course this approach cannot be applied to retrieved implants because the original weights of the implants are unknown and the implants may show added weight through embedded thirdbody particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With followup exceeding 12 years, the incidence and extent of osteolysis have been markedly lower for hip arthroplasties using crosslinked PEs [5,27,28]. This outcome contradicts the predictions by some early studies [11,18,25], which indicated the osteolytic potentials with elevated crosslinking could be as high as or higher than for historical PEs. Our results indicated this misprediction was in great part due to inherent limitations of the protocols used to isolate and characterize the PE wear particles generated in laboratory wear simulations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [34] raised concerns that these morphologic characteristics of the wear particles might affect macrophage response and osteolysis. These concerns are reinforced by the results of studies that show increased in vitro bioactivity with the HCLPE particles [16,26]. Only longer followup studies will clarify these questions.…”
Section: Discussionmentioning
confidence: 99%